Redefining late renal artery revascularization - splenorenal bypass in the treatment of acute renal artery occlusion - Mendes,Daniel A. (2022)
Abstract Introduction: The ischemic window of kidney parenchyma is narrow, so a rapid development of renal infarction after acute renal artery occlusion is expected. However, patients often present with nonspecific symptoms and laboratory findings, making the early diagnosis challenging and contributing to treatment delay. Irreversible kidney dysfunction seems not to depend on the total warm ischemia time alone, and other factors could play a role. Case report: A 64-year-old male with chronic kidney disease presented to the emergency department with acute kidney injury of unknown etiology. Unfavorable evolution demanded the initiation of hemodialysis due to refractory hypervolemia and resistant high blood pressure some days later. A computed tomography angiography showed aortoiliac occlusion starting below the superior mesenteric artery, conditioning the occlusion of the proximal segment of both renal arteries. A splenorenal retrocaval bypass was done uneventfully, 21 days after the initial presentation, to revascularize the right kidney. After surgery, the patient showed marked improvement of diuresis with decreased nitrogen retention parameters, allowing definitive suspension of the dialysis technique in the first post-operative week and controlled blood pressure. Serum creatinine dropped to baseline and remained stable at one year of follow-up. Chronic limb-threatening ischemia developed later in the left lower limb, and the patient was revascularized with an axillobifemoral bypass. Conclusion: Our case highlights the benefit of aggressive late renal revascularization in selected patients with acute renal artery occlusion who maintain residual tubular function and some perfusion of kidneys despite proximal occlusion of the renal artery. More extensive studies would be essential to provide adequate patient selection and management recommendations.